Huntington Disease Health Related Quality of Life, Function and Well Being: The Patient’s Perspective - Jesús Pérez-Pérez; Sofía García-López; Tamara Fernández Valle; Cèlia Painous; Maria Rosa Querol-Pascual; Pedro J. García Ruiz; Elena Bellosta Diago; Esther Cubo Delgado; Barbara Vives Pastor; María Carmen Peiró Villaplana; Idaira Martín Santana; Marta Blázquez Estrada; et al. (Neurology and Therapy)
Abstract Background Limited information is available on patients' experience living with Huntington’s disease (HD). The primary objective of this study was to assess the health-related quality of life and well being of patients with HD. Methods A non-interventional, cross-sectional study was conducted in 17 hospitals-based movement disorders units in Spain. Patients aged ≥ 18 years, genetically HD diagnosed [with a diagnostic confidence level score of 4, and an Independence Scale (IS) score ≥ 70] were included. The primary variables were the Huntington's Disease Health-related Quality of Life (HDQLIFE) scores and results of the Satisfaction with Life Scale (SWLS). Secondary outcomes include the Unified HD Rating Scale (UHDRS), Beck Hopelessness Scale (BHS), Stigma Scale for Chronic Illness (SSCI-8), Beck Depression Inventory-Fast Screen (BDI-FS) and Problem Behaviours Assessment for HD short Version (PBA-S). Results A total of 102 patients were included. The mean age (SD) was 53.1 (12.1) years and 56% were male. Most of the patients (99.0%) showed motor symptoms (87.3%), behavioural and psychiatric disturbances (59.8%), or cognitive impairment (20.6%). HDQLIFE domain score means (SD) includes concern with death and dying 45.97 (9.60) end-of-life planning 37.91 (8.84), and meaning and purpose 44.74 (9.05). SWLS score mean was 24.25 (7.33). Depressive symptoms were found in 37.4% of patients and moderate-to-severe feelings of hopelessness in 32.9%. The prevalence of stigma was 55.9% (n = 57). Conclusion HD impacted quality of life, with prevalent motor, psychiatric symptoms and cognitive impairment. Patient perspectives may provide complementary information to implement specific interventions.